The punctuation of Hebrews 10:2 and its significance for the date of Hebrews - Church, Philip (Tyndale bulletin, 2020)
The significance of Hebrews 10:2 for the date of the letter has been the subject of debate, with some scholars finding it decisive for a pre-70 CE date and others denying it any importance, proposing (rightly) that the writer is arguing theoretically about sacrificial activity extending since the time of Aaron. The 2017 publication of the Tyndale House Greek New Testament brings the debate into sharp focus with Hebrews 10:2a punctuated as a statement (‘If the sacrifices were effective, they would not have ceased to be offered’) rather than a question (‘If the sacrifices were effective, would they not have ceased to be offered?’). Reading the clause as a statement implies that the temple has fallen and sacrifices have ceased, leading to the conclusion that Hebrews postdates this event. An examination of the manuscript evidence, the history of interpretation, the syntax, and the context shows that the clause should be read as a rhetorical question expecting a positive answer from the readers: ‘Yes, the sacrifices would have ceased if they were effective.’ Even if the writer were arguing theoretically, this would be a difficult answer had the temple been destroyed. This makes a pre-70 date more likely than a post-70 date.